International teacher education promising pedagogies. (Part B) - Craig, Cheryl J.; Orland-Barak, Lily. (Bingley, U.K. : Emerald, 2015)
All countries in the world understand that education is vital to human and economic prosperity and that teacher education unavoidably is implicated. But the snag is this: political forces shaping public opinion in individual nations (particularly the U.S.) are deeply divided concerning how teacher education should proceed. This book acknowledges this Achilles heel tension, but does not become weighed down by it. Instead, it focuses on 'the practical' (Schwab, 1969), matters that have been locally deliberated and enacted. Pedagogies are named, origins (cultural/practical/theoretical/policy roots) are traced and a live example of the pedagogy unfurling in the local setting is presented from an insiderview.
Teacher education pedagogies related to preparing preservice teachers as leaders in Pakistan / Meher Rizvi -- Preservice teachers' professional growth as leaders : empowerment through research-oriented reflective practice and didactic expertise in Germany / Bianca Roters -- Developing preservice teachers as leaders : a case of early childhood education in Hong Kong / Issa Danjun Ying, Dora Ho -- Empowering principals and teachers to develop participatory teacher leadership in Cyprus : toward a meta-modern paradigm of teacher and preservice teacher development / Mary Koutselini -- Pedagogies of working with diversity : research as teacher education : learning about student diversity through narrative inquiry / Elaine Chan -- Pedagogies of working with diversity : doing, knowing, being, belonging, becoming / Penny Haworth -- Pedagogies of working with diversity : West-East reciprocal learning in preservice teacher education / Shijing Xu, Shijian Chen, Ju Huang -- Informing preservice teacher education pedagogies through in-service professional development on cultural diversity in Turkey / John McKeown -- Pedagogy for aboriginal students in the U.S. : shattering walls of distorted glass / Beverly J. Klug -- Conditions and characteristics of partnership between teachers and parents : from legislation to challenges of common practice in Slovenia / Jana Kalin -- Walking alongside : a pedagogy of working with parents and family in Canada / Debbie Pushor -- Pedagogies of social justice : an Indian case / Tara Ratnam -- Teacher education for dialogue across difference : an example from Israel / Freema Elbaz-Luwisch -- Promoting social justice in Swedish teacher education / Silvia Edling, Anneli Frelin -- Pedagogies of working with technology in Spain / Carlos Marcelo, Carmen Yot -- Learning, arts, and technology : creating animations in teacher education in Brazil / Martha Prata-Linhares, Ana Paula Bossler, Pedro Caldeira -- Using video in teacher education : an example from the Czech Republic / Eva Minar<U+030c>kova<U+0301>, Michaela Pis<U+030c>ova<U+0301> , Toma<U+0301>s<U+030c> Jank -- Pedagogies of working with technology in Switzerland / Bernadette Charlier, Pierre-Franc<U+0327>ois Coen -- Preparing teachers for tomorrow's schools : reforming initial teacher education with the use of ICT in Norway / Trond Eiliv Hauge -- International teacher education : promising pedagogies concluding chapter / Lily Orland-Barak, Cheryl J. Craig.
Print version record
Keywords: Education -- General; Teaching skills & techniques; Teachers -- Training of; Education -- Study and teaching